1988
DOI: 10.1136/adc.63.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Joint mobility and motor development.

Abstract: SUMMARY The association of joint hypermobility and motor development was sequentially investigated in 715 infants from the ages of 8 to 14 months. Seven joints were evaluated for mobility, and each infant underwent a physical and neurological examination. Parents were given a Denver Developmental Parents' Questionnaire. All subjects with a general developmental delay, systemic illness or syndrome were excluded. The infants were classified as having normal or delayed motor development with normal or delayed joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
2
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 6 publications
3
29
2
1
Order By: Relevance
“…We found a delay in motor development in 56% of children younger than three years of age, whereas Jaffe et al 18 reported a delay in about 30% in a group of 715 children between eight and 14 months of age. Davidovitch et al 30 reported, as we also found in our study, no relationship between generalized joint hypermobility and gross and fine motor performance in children between five and seven years of age.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…We found a delay in motor development in 56% of children younger than three years of age, whereas Jaffe et al 18 reported a delay in about 30% in a group of 715 children between eight and 14 months of age. Davidovitch et al 30 reported, as we also found in our study, no relationship between generalized joint hypermobility and gross and fine motor performance in children between five and seven years of age.…”
Section: Discussioncontrasting
confidence: 57%
“…Some authors stated that in early childhood a delay in motor development is present with catch up in most children before the age of two years, while others stated that gross and fine motor development remained significantly delayed in children who exhibited joint hypermobility and motor delay in infancy. 18,19 Multiple explanations for the motor delay in infancy exist. As early as birth, congenital benign hypotonia or floppy infant syndrome and hypermobility of the joints have been associated with each other.…”
Section: Introductionmentioning
confidence: 98%
“…Six months later, 75.9% of the infants with HMS no longer had hypermobility; 83.3% of these infants caught up in motor development, whereas only 54.5% of the infants who remained hypermobile caught up. 43 At 5 years of age, children who had hypermobility and motor delay at age 18 months were 3 times as likely as other children to have motor delay. 44 Other reports have shown no motor delay in elementary school children with HMS.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Disease-related pro®les have been suggested or established in hypermobile children [9], in visually handicapped children [1], in children with Down syndrome [11], even in patients with neurological syndromes [10]. We observed that the severity of OI in¯uences age and sequence of achieving motor milestones signi®-cantly.…”
Section: Discussionmentioning
confidence: 80%